Diagnostics and treatment of dysphagia: clinical guidelines of the Russian gastroenterological association - V. T. Ivashkin; I. V. Mayev; A. S. Trukhmanov; T. L. Lapina; A. A. Sheptulin; O. A. Storonova; D. N. Andreev (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
.